English Language Teaching Methodology. - Бортник, Світлана Борисівна (Universitatea de Stat „Bogdan Petriceicu Hasdeu” din Cahul, 2024)
The article defines different types of assessment, characterizes the main components of monitoring students' educational activities. The issue of the feasibility of using various types of control and assessment in professionally oriented foreign language training for students majoring in natural and technical disciplines is considered. Performing authentic tasks is one of the components of the professional training of a modern specialist in any field. Methodological approaches to the evaluation process in preparation for professional communication in a foreign language environment were studied.
Keywords: types of control and assessment, professionally oriented foreign language learning, feedback, integration of foreign language learning and the main subject